2006
DOI: 10.1089/scd.2006.15.260
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Stromal Cell–derived Factor-1 Enhances Endothelium-supported Transmigration, Maintenance, and Proliferation of Hematopoietic Progenitor Cells

Abstract: To clarify the direct effects of aberrant overexpression of stromal cell-derived factor-1 (SDF-1) by the human endothelium on circulating progenitor cells, we overexpressed the SDF-1 gene in human umbilical vein endothelial cells using an adenoviral vector (HUVEC/AdeSDF-1) and examined the endothelium-supported trafficking and growth of hematopoietic progenitor cells (HPCs) in mobilized peripheral blood (mPB). In culture, the HUVEC/AdeSDF-1 monolayers induced the migration of mPB CD34(+) cells underneath the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…SDF-1 is key in recruitment of monocytes/macrophages and their perivascular retention around new blood vessels that arise from neovascularlization 12 . SDF-1 mediates proliferation, adhesion, migration, and homing of circulating progenitor cells that express the SDF-1 receptor CXCR4 and monocytes, thereby promoting tissue regeneration 4, 18, 49 . Further, SDF-1 causes proliferation of CD34+ cells and differentiation of these cells into macrophages and foam cells 48 .…”
Section: Discussionmentioning
confidence: 99%
“…SDF-1 is key in recruitment of monocytes/macrophages and their perivascular retention around new blood vessels that arise from neovascularlization 12 . SDF-1 mediates proliferation, adhesion, migration, and homing of circulating progenitor cells that express the SDF-1 receptor CXCR4 and monocytes, thereby promoting tissue regeneration 4, 18, 49 . Further, SDF-1 causes proliferation of CD34+ cells and differentiation of these cells into macrophages and foam cells 48 .…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9]16,24 Enhanced SDF-1 expression and production in the endothelium is essential for the engraftment of human stem cells and for their maintenance in situ. 7,8,20,25 Ex vivo exposure of EPCs to SDF-1 before their injection would be expected to enhance their recruitment from the circulation to ischemic tissue and, thus, their graft efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, normal human synovium (n ϭ 11) showed minimal VEGF-A staining ( Figure 1D). Because mobilization of EPCs and proangiogenic HPCs from the BM requires activation of MMPs, particularly MMP-9, and because SDF-1␣ has been shown to potently promote the migration and activation of mononuclear cells, including HPCs, 25,26 we stained HJD and control synovium for these mediators. We observed that MMP-9 ( Figure 1B) and SDF-1␣ ( Figure 1C), were highly expressed in the vascular endothelium, with moderate expression in synovial cells in the lining and sublining regions of the hemophilic synovium (n ϭ 12).…”
Section: Hjd Synovium Expresses Proangiogenic Mediators and Myeloid Cmentioning
confidence: 99%